‘Candidatus Cochliophilus cryoturris’ (Coxiellaceae), a symbiont of the testate amoeba Cochliopodium minus - Tsao, Han-Fei (Sci Rep, 2017)
Free-living amoebae are well known for their role in controlling microbial community composition through grazing, but some groups, namely Acanthamoeba species, also frequently serve as hosts for bacterial symbionts. Here we report the first identification of a bacterial symbiont in the testate amoeba Cochliopodium. The amoeba was isolated from a cooling tower water sample and identified as C. minus. Fluorescence in situ hybridization and transmission electron microscopy revealed intracellular symbionts located in vacuoles. 16S rRNA-based phylogenetic analysis identified the endosymbiont as member of a monophyletic group within the family Coxiellaceae (Gammaprotebacteria; Legionellales), only moderately related to known amoeba symbionts. We propose to tentatively classify these bacteria as ‘Candidatus Cochliophilus cryoturris’. Our findings add both, a novel group of amoeba and a novel group of symbionts, to the growing list of bacteria-amoeba relationships.